Tailored nanofiber composites for a flexible piezoelectric nanogenerator: Poly(vinylidene fluoride) with BaTiO3/NiFe2O4 - Hemalatha Parangusan (6556133) (2024)
Owing to the depletion of fossil fuel energy and the pollution caused by chemical batteries, as well as the growing number of electronic devices and the Internet of Things (IoT), there is a greater demand for power devices that are lightweight, inexpensive, durable, and sustainable. An excellent alternative is a self-sufficient, adaptable piezoelectric energy harvester, easily integrated with small electronics to generate real-time, sustained energy. This study develops a piezoelectric nanogenerator (PENG) by uniformly drawing spun membranes containing 2 wt% of barium titanate (BaTiO3) and nickel ferrite (NiFe2O4). The flexible piezoelectric nanogenerator was prepared by electrospinning technique. The electroactive phase content of PVDF is increased by adding nanofillers, and the interfacial polarization between the nanofiller and polymer matrix is significantly enhanced. The obtained electrospun nanofibers were evaluated for mechanical flexibility and piezoelectric responses. The findings demonstrated that, for a given filler composition, the output voltage achieved was more significant than the voltage generated by the pure PVDF. The PVDF/BaTiO3-NiFeO4 electrospun nanofibers demonstrated the highest piezoelectric peak-to-peak output voltage of 4.1 compared to pure PVDF (∼125 mV). From these results, the prepared electrospun polymer nanocomposite fibers may be preferred as the energy-converting devices that can be applied to flexible and wearable electronics. The materials mechanical, breakdown strength and dielectric characteristics align with their potential uses in wearable electronics. Other Information Published in: Journal of Alloys and Compounds License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jallcom.2024.174254